Underestimating the size of the problem? UK anaesthesia for patients with obesity. Issue 6 (November 2017) - Palmer, James; Sury, Mike; Nightingale, Claire; Pandit, Jaideep; Cook, Tim; ,
Summary: We analysed data from 14, 000 patients in the 2013 United Kingdom Anaesthesia Activity Survey of the Fifth National Audit Project of the Royal College of Anaesthetists and Association of Anaesthetists of Great Britain and Ireland to examine anaesthetic, organisational and clinical practice for patients with obesity. We compared practice then with current guidance on management of this patient group. Obesity was reported in 22%, mainly Black, Afro-Caribbean and White Caucasian patients. There was minimal variation in surgical timing, anaesthetic seniority, induction location or day-case procedure rates. As BMI increased above 25 kg m −2 ASA grade rose and there were modest changes in practice towards that recommended for this patient group. Some practice changes were counter-intuitive. When BMI exceeded 35 kg m −2 safety based practice changed markedly. For patients receiving GA there was an increase in immediate (operative) mortality as BMI rose. UK anaesthetic practice in 2013 appears to underestimate patient levels of obesity, does not reflect recent published guidelines for the management of patients with obesity undergoing anaesthesia and, taken with the mortality findings, raises concerns over the reliability of safe management of such patients.